IMPROVING STUDENT'S LEARNING MOTIVATION WITH NUMBERED HEAD-TOGETHER LEARNING MODEL ON THE THEME OF CLEAN AIR FOR HEALTH IN CLASS VA SD NEGERI 107405 SEI ROTAN - Dila Azhari (Sean Institute, 2021)
The problem in this research is the low learning motivation of students on the theme of Clean Air for Health, especially the science content. This study aims to increase students' learning motivation on the piece of Clean Air for Health, especially science content, by using the Numbered Head Together learning model in class VA of SD Negeri 107405 Sei Rattan. This study uses the design of CAR (Classroom Action Research) with the learning model of Numbered Head Together. The subjects in this study were all students of class VA SD Negeri 107405 Sei Rattan for the 2018/2019 academic year, totaling 40 people. This research was carried out in two cycles, namely, cycle I and cycle II. Each process consists of 4 stages: planning, implementing actions, observing, and reflecting. The data collection technique used in this study was an observation sheet on student motivation and an observation sheet on implementing the Numbered Head Together learning model. The data analysis technique used is a qualitative, quantitative, and descriptive data analysis technique.